“Reinventing” Higher Education – Rhetoric versus Reality in a Post-Pandemic World - Murgatroyd, Stephen (REVISTA PARAGUAYA DE EDUCACIÓN A DISTANCIA (REPED), 2022)
The future of colleges and universities in the post-pandemic world is a matter of much speculation and debate. UNESCO has suggested a framework for the future which, while focused, does not fully reflect the realities faced by these institutions – declining public investment, declining public trust, challenges to integrity and free speech and growing commercialization of formerly creative and independent work. An alternative framework – that of the college or university as a permanently failing organization – is presented as a way of interpretation the current reality and this is contrasted with the UNESCO propositions.